(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
Agriculture is critical to the economies of most states in Nigeria, Kwara included, with maize being an important food crop. However, geographic variation in soil qualities and inconsistencies in maize yields across the states are becoming increasingly concerning. The spatial variability of major soil physical and biological properties in Asa and Moro Local Government Areas (LGAs) was investigated utilizing a cross-sectional design, current Geographic Information Systems (GIS), and geostatistical approaches. Soil samples were collected at 70 geo-referenced locations and analyzed for texture, bulk density, porosity, moisture content, microbial biomass, and organic carbon. Data were mapped using ArcGIS 10.7 to assess spatial trends and identify management zones. The results revealed significant differences between the two LGAs. Asa LGA had higher moisture content (46.74%), porosity (49%), organic carbon (1.6%), and phosphorus (24.5 mg/kg) but lower pH (5.4 in water; 4.5 in CaCl2) and higher erosion risks. Moro LGA, by contrast, showed higher pH (6.4 in water; 5.3 in CaCl2), bulk density (1.29 gcm-3), and hydraulic conductivity (23.5 mmhr-1). Tailored management strategies, such as lime application in Asa and organic amendments in Moro, are crucial. These findings highlight the need for precision agriculture and site-specific management strategies in addressing soil variability and maximizing resource usage and maize yields in both LGAs.